Amorphization and modified release of ibuprofen by post-synthetic and solvent-free loading into tailored silica aerogels. (31st December 2022) - Zarinwall, Ajmal; Maurer, Viktor; Pierick, Jennifer; Oldhues, Victor Marcus; Porsiel, Julian Cedric; Finke, Jan Henrik; Garnweitner, Georg
Abstract: Promising active pharmaceutical ingredients (APIs) often exhibit poor aqueous solubility and thus a low bioavailability that substantially limits their pharmaceutical application. Hence, efficient formulations are required for an effective translation into highly efficient drug products. One strategy is the preservation of an amorphous state of the API within a carrier matrix, which leads to enhanced dissolution. In this work, mesoporous silica aerogels (SA) were utilized as a carrier matrix for the amorphization of the poorly water-soluble model drug ibuprofen. Loading of tailored SA was performed post-synthetically and solvent-free, either by co-milling or via the melting method. Thorough analyses of these processes demonstrated the influence of macrostructural changes during the drying and grinding process on the microstructural properties of the SA. Furthermore, interfacial SA-drug interaction properties were selectively tuned by attaching terminal hydrophilic amino- or hydrophobic methyl groups to the surface of the gel. We demonstrate that not only the chemical surface properties of the SA, but also formulation-related parameters, such as the carrier-to-drug ratio, as well as process-related parameters, such as the drug loading method, decisively influence the ibuprofen adsorption efficiency. In addition, the drug-loaded SA formulations exhibited a remarkable physical stability over a period of 6 months. Furthermore, the release behavior is shown to change considerably with different surface properties of the SA matrix. Hence, the reported results demonstrate that utilizing specifically processed and modified SA offers a compelling technique for enhancement of the bioavailability of poorly-water soluble APIs and a versatile adjustment of their release profile. Graphical Abstract: UF0001